Improved maximal strength is not associated with improvements in sprint time or jump height in high-level female football players: a cluster-randomized controlled trial - Sigurd Pedersen; Kim Arne Heitmann; Edvard H. Sagelv; Dag Johansen; Svein Arne Pettersen (BMC, 2019)
Abstract Background Maximal strength increments are reported to result in improvements in sprint speed and jump height in elite male football players. Although similar effects are expected in females, this is yet to be elucidated. The aim of this study was to examine the effect of maximal strength training on sprint speed and jump height in high-level female football players. Methods Two female football teams were team-cluster-randomized to a training group (TG) performing maximal strength training (MST) twice a week for 5 weeks, or control group (CG) doing their regular pre-season preparations. The MST consisted of 3-4 sets of 4-6 repetitions at ≥85% of 1 repetitions maximum (1RM) in a squat exercise. Sprint speed and jump height were assessed in 5-, 10- and 15 m sprints and a counter-movement jump (CMJ) test, respectively. Nineteen participants in TG (18.3 ± 2.7 years) and 14 in CG (18.3 ± 2.4 years) completed pre- and posttests and were carried forward for final analyses. Results There was no improvement in neither of the sprint times (p > 0.36), nor jump height (p = 0.87). The players increased their 1RM in squats (main of effect of time: p < 0.00, pη2 = 0.704), and an interaction effect of time x group was observed (p < 0.00, pη2 = 0.516) where the TG increased their 1RM more than the CT (between subjects effects: p < 0.001, pη2 = 0.965). Conclusions MST improved maximal strength in female football players to a large extent; however, the improvement in maximal strength did not result in any transference to sprint speed or jump height. Trial registration This study was registered at clinicaltrials.gov PRS (Protocol registration and results System) with the code NCT04048928, 07.08.2019, retrospectively registered.